An investigation on thermal conductivity of fly ash concrete after elevated temperature exposure. (1st September 2017) - Wang, Wei; Lu, Caifeng; Li, Yunxia; Li, Qingtao
Highlights: The effects of a range of micro-environment relative humidity were investigated. Fly ash improved the concrete properties after exposed to elevated temperature. Concrete showed quite a few defects after exposure to 550 °C. Abstract: The influence of high temperature on concrete is closely related to the thermal conductivity of concrete. In this paper, the influence of high temperature and micro-environment relative humidity on the thermal conductivity of fly ash concrete were investigated. A high-temperature energy-saving electric resistance furnace and an artificial climate chamber were used to achieve different high temperature and micro-environment relative humidity in specimens, respectively, and the thermal conductivity of specimens were test by thermophysical properties analyzer. The results showed that after exposed to high temperature, the compressive strength and thermal conductivity of both ordinary concrete and fly ash concrete were markedly reduced, and when the specimens were subjected to 550 °C, the compressive strength reduced about 26%. With an increase in micro-environment relative humidity, the thermal conductivity of both ordinary concrete and fly ash concrete were increased and when the relative humidity reached 100%, the thermal conductivity increased about 22%. Under same conditions, the thermal conductivity of fly ash concrete with 30% fly ash replacement was lower than that of ordinary concrete.